The THE EFFECT OF TALKING STICKS TO IMPROVE STUDENT’S SPEAKING SKILL AT VOCATIONAL STUDIES OF IPB UNIVERSITY: THE EFFECT OF TALKING STICKS TO IMPROVE STUDENT’S SPEAKING SKILL AT VOCATIONAL STUDIES OF IPB UNIVERSITY - Marithasari, Harries; Soelistiyowati, Renny; Bachtiar, Willy; Vibowo, Heryudianto; Bayu Suriaatmaja Suwanda; Sesar Husen Santosa; Firman Muhammad Basar (The Journal Of English Teaching For Young And Adult Learners, 2024)
The goal of this study was to ascertain the Talking Sticks method of English language learning, which is used in the English for Communication course at IPB University's Vocational School. An experimental methodology is applied. Qualitative research is the kind that this is. Tests and interviews were used as methods of data gathering. Three hundred students from the Vocational School of IPB University's Digital Communication and Media Study Program served as the research subjects. The study's findings indicate that people's speaking abilities were valued more highly. Pre-test scores average 74, post-test scores average 77 for the control group and 89 for the experimental group. It is clear from this procedure that Talking Sticks can be utilized as a learning tool to improve speaking abilities. Lecturers are able to observe how the methods of learning that are employed can improve students' English comprehension. Additionally, it is known from the interview process that professors can identify candidates with strong and weak talents by using the results of the pre- and post-tests.